Peran Kepolisian dalam Penyidikan Tindak Pidana Korupsi (Studi pada Kepolisian Daerah Sumatera Utara) - Siahaan, Herikson Parulian; Marlina, Marlina; Zul, Muaz (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
The purpose of this study was to determine how the role of the police in the investigation of corruption, how the authority of the police in investigating corruption and how the obstacles faced by the police in investigating corruption in the North Sumatra Regional Police. This research is directed towards normative juridical legal research or doctrinaire which is also referred to as library research or document study because more is done on secondary data in the library. Normative or doctrinaire legal research proposed in this study is a study of legal principles by conducting research in the North Sumatra Regional Police. The results of the research and discussion explaining the regulation of the role of the police in investigating criminal acts of corruption are found in Law No. 8 of 1981 concerning the Criminal Procedure Code, Law No. 31 of 1999 concerning Corruption Crimes as amended by Law No. 20 of 2001 and Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia, in which of all the arrangements explained that the investigator included in the corruption case was the Republic of Indonesia's National Police Officer.